Internalization of Islamic Education Values in the Pancasila Student Profile Strengthening Project through a Multidisciplinary Approach - Uroidli, Ali; Faizin, Moh.; Aziz, Yahya; Yudi, Usman (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
This research aims to explore the internalization of Islamic values in the Pancasila Student Profile Strengthening Project at SMA Negeri 1 Gedangan, Sidoarjo Regency. The focus of the research was the eleventh-grade odd-semester students using a case study approach. The research method used was descriptive qualitative. The data collecting techniques employed were observation and interviews with various informants, such as the principal, curriculum representative, project assistant teacher, and Islamic religious education teacher. The researchers conducted data analysis using the Miles and Huberman analysis method to reduce data, present data, and draw conclusions. The results showed the importance of the integration of Islamic values in student character education at SMA Negeri 1 Gedangan, making a significant contribution to understanding Islamic education strategies to strengthen Pancasila values at the senior high school level.